The physicochemical and catalytic properties of clay extrudates in cyclization of citronellal - Vajglová Zuzana; Simakova Irina L.; Eränen Kari; Mäki-Arvela Päivi; Kumar Narendra; Peurla Markus; Tolvanen Stiina; Efimov Alexander; Hupa Leena; Peltonen Jouko; Murzin Dmitry Y. (Elsevier B.V., 2022)
Four clay materials, namely, bentonite, bleaching earth, attapulgite and sepiolite, were shaped into the cylindrical body by extrusion. Clays were characterized in depth by TEM, SEM-EDX, N2 physisorption, pyridine FTIR, pH measurements, contact angle measurements, 27Al MAS NMR, and the crush test. Catalytic properties were investigated in the citronellal cyclization as a model reaction. The reaction was performed in the trickle-bed reactor at 70 °C, 10 bar of Ar with 0.086 M initial citronellal concentration in cyclohexane. The best results were obtained over attapulgite with isopulegols yield of 24% and stereoselectivity to the desired isopulegol isomer of 61%. Attapulgite had the highest meso-to-micropore volume ratio, the highest basicity, a low Brønsted-to-Lewis acid sites ratio, and the lowest amount of Brønsted acid sites compared to other extrudates. In addition, same clay exhibited the highest mechanical strength of extrudates.